Lexematic change as anthropological sign, in two versions of a tradicional story - Coto de Attilio, Patricia H. (2009)
This paper analyzes a new version of the well-known story “The wicked blacksmith and the Devil”, spread around a semi-urbanized area inhabited by migrants from the Argentine coastal zone. The starting point is the concept of meta-code as a specific group interaction mode. Oral narratives may be considered as part or expressions of such meta-codes and, therefore, their analysis will be more complex, in order to understand the text within its contexts and in its ideological context. It is necessary, then, to resort to a narratological methodology which rescues oral narratives' discursive strategies, as well as to a linguistic and semiotic methodology which rescues pronouncements and observes their significance with respect to intertextual, extratextual and contextual relations.